Оцінка діяльності страхових посередників на страховому ринку України - Рубцова, Наталя Миколаївна; Рубцова, Наталья Николаевна; Rubtsova, Natalia (My University, 2020)
UK: Вивчено основні канали продажу договорів страхування як на вітчизняному страховому ринку так і за кордоном. Розглянуто діяльність найбільших світових та українських страхових брокерів. Проаналізовано сучасний стан функціонування страхового посередництва в Україні, зокрема досліджено динаміку кількості укладених договорів страхування та зібраних страхових премій за допомогою страхових посередників, представлено суми їх комісійних винагород. Досліджено роботу міжнародних перестрахових брокерів та перспективи виходу вітчизняних брокерів на зовнішні страхові ринки. Надані певні пропозиції щодо покращення роботи страхового посередництва в Україні та приведення його у відповідність із європейськими нормами. EN: This article examines the international market of insurance services, which has extensive experience in insurance intermediation, namely insurance agents and brokers. It was found that the poor work of insurance intermediaries leads to the fact that consumers do not have enough information about the full range of insurance services, and insurers themselves do not have a complete picture of the demand for insurance services. To this end, an analysis of the current state of insurance intermediation in Ukraine, based on which we can say that in recent years there has been a tendency to reduce the number of insurance companies in Ukraine, and hence the growth of insurance intermediaries per 1 domestic insurer. It is established that the domestic market of insurance intermediation is underdeveloped and does not yet meet world standards and trends. The main indicators of the market of insurance mediation in Ukraine are analyzed, in particular, the dynamics of the number of concluded insurance contracts and collected insurance premiums with the help of insurance intermediaries is studied, the amounts of their commissions are presented. One of the most important tasks was to determine the features of the work of insurance brokers and intermediaries in Europe. The rating of the world's largest insurance brokers by the amount of profit is considered. An analysis of the indicators of the number of insurance brokers in Ukraine, which showed that there is a certain imbalance between the number of insurance companies and insurance brokers. Some proposals have been made to improve the work of insurance intermediation in Ukraine and bring it in line with European standards.
Assessment of activity of insurance intermediaries in the insurance market of Ukraine
Keywords: страховий ринок; страхове посередництво; страхові агенти; страхові та перестрахові брокери; канали просування страхових продуктів; insurance market; insurance intermediation; insurance agents; insurance and reinsurance brokers; channels for promoting insurance products